A Review on the Resilient Response of Unsaturated Subgrade Soils - Xuanxuan Chu (Advances in Civil Engineering)
Considering the great contribution of subgrade modulus to the overall performance of roads or railways, it is crucial to provide the best prediction of resilient modulus for their foundations. Incorporating the seasonal variation of moisture content, the resilient modulus variation of unsaturated soils will be accurately predicted. This paper aims to introduce and discuss the knowledge about resilient response of unsaturated soils and emphasize the effects of humidity. A literature review on resilient response of unsaturated soils is presented based on the previous studies. The affecting factors (i.e., wetting and drying, moisture content, and matric suction) were discussed. The prediction model development of the resilient response of unsaturated soils was presented. The limitations and advantages of the model were analyzed and compared. It reveals that the current models were limited regarding stress conditions, moisture content, matric suction, and soil types, and further studies are still needed to achieve a better understanding of resilient response of unsaturated soils.